Preliminary Study of Heavy Metals of Cymodocea rotundata in Doreri Bay Manokwari Regency - Luky Sembel; Dwi Setijawati; Defri Yona; Emmanuel Manangkalangi; Philipus Musyeri; Yenny Risjani (Musamus Fisheries and Marine Journal, 2021)
Sources of activity in Dorei Bay come from the Sanggeng market, the Wosi market, the port, the PLTD (Diesel Power Plant), hospitals, hotels, and residential areas. The seagrass system has a function as a food provider, as primary productivity in waters, dampers the arrival of waves, a place for growth and development of biota and sediment traps. Research and information on the accumulation of heavy metals in seagrass, especially Cymodocea rotundata are still very limited, especially in Doreri Bay. This study aims to describe the accumulation of heavy metals in seagrass Cymodocea rotundata, including leaves, roots, and rhizome, comparing the accumulation of heavy metals in seagrass Cymodocea rotundata each location as well as knowing the pollution index of each location. The research was conducted in Doreri Bay, Manokwari, West Papua in August 2018. The sampling locations for Cymodocea rotundata seagrass were around the waters of Pelayaran, Wosi, Yankarwar, Anggrem, and Nusmapi Island. The results showed that the highest Cu concentrations were described from each location, which ranged from 18.75 to 28.64 (mg.kg-1), followed by heavy metal Pb ranging from 0.46-19.31 (mg.kg-1), then logm weight of Cd ranged from 1.11-4.97 (mg.kg-1) and the lowest Cr6 + concentration in each location ranged from 0.20 -0.52 (mg.kg-1). The percentage of metal concentrations in the roots and rhizomes is 50%, it can even reach 82.64%, namely Pb metal at Yankarwar Beach. Meanwhile, the metal concentration in the leaf area ranged between 17.36-50.00% and the highest proportion was found in Pb metal at the Pelayaran location and Cr6 + metal at the Wosi location. The calculation results of the Metal poluttion Index (MPI) for heavy metals Pb, Cd, Cu, and Cr6 + show that the highest heavy metal index of 5 locations is on Anggrem Beach and the lowest is at Pelayaran Beach